A greenness evaluation of deep eutectic solvents-based conventional extraction methods for elemental determination by spectrometry techniques - Costa, Floriatan Santos; Moreira, Luana Santos; da Silva, Erik Galvão Paranhos; Gonzalez, Mario Henrique [UNESP]; Amaral, Clarice D.B. (Elsevier, 2024)
Sample preparation for elemental determination remains challenging, complex, and environmentally problematic. Recent advancements have been achieved by utilizing deep eutectic solvents (DES) in conventional extraction methods applied to many matrices and this article provides an evaluation of these applications. The DES-based methods were evaluated for their greenness using the analytical greenness metric (AGREE) and the analytical greenness metric for sample preparation (AGREEprep). The methods comparisons were conducted through exploratory data analysis using a self-organizing map (SOM) to relate the parameters of the methods, characteristics and relations between variables, and associate the data with the AGREE and AGREEprep scores. This review enhances understanding of the implications linked to incorporating DES into sample preparation methods, offering insights for enhancing sustainability and performance in future applications.
Keywords: Extraction; Green analytical chemistry; Greenness metrics; Sample preparation; Self-organizing map; Spectrometry